Clinical Characteristics and Prognosis of Patients with End-Stage Hypertrophic Cardiomyopathy from a Tertiary Center Cohort: Systolic Dysfunction and Advanced Diastolic Dysfunction - Andreea Sorina Afana; Robert Daniel Adam; Sebastian Militaru; Sebastian Onciul; Oana Andrei; Adela Chirita Emandi; Maria Puiu; Constantin Militaru; Ruxandra Jurcut (Diagnostics)
Background: Hypertrophic cardiomyopathy (HCM) is a genetic disorder marked by myocardial hypertrophy, leading to diastolic and systolic dysfunction and heart failure. Traditionally, the burn-out stage is defined by systolic dysfunction, but we propose expanding its definition to include advanced diastolic dysfunction. Methods: We retrospectively analyzed HCM patients (2004–2023) with either systolic dysfunction (left ventricular ejection fraction [LVEF] < 50%) or advanced diastolic dysfunction (preserved LVEF with left atrial enlargement and elevated filling pressures: E/A ≥ 2 or E/e′ ≥ 14). Both subgroups were included under the term “end-stage HCM” and compared to HCM controls with preserved LVEF and impaired relaxation. Results: Of 696 HCM patients, 94 had end-stage HCM (23 with systolic dysfunction, 71 with advanced diastolic dysfunction). Median age was 56.5 years, and 55.3% were male. End-stage HCM patients were more symptomatic at follow-up than controls (91.5% vs. 75.0%, p-value = 0.006), with higher rates of dyspnea and advanced heart failure (38.3% vs. 6.3%, p-value < 0.001). Advanced diastolic dysfunction was associated with a more symptomatic profile (p-value = 0.013) and a high annual mortality rate (2.34%, p = 0.014). Male sex, older age, lower LVEF, and higher E/A predicted systolic dysfunction. Conclusions: Advanced diastolic dysfunction represents an alternative progression pathway in burn-out HCM, requiring distinct management strategies alongside systolic dysfunction.